Libby, Montana [videorecording (DVD)] - Carr, Drury Gunn; Hawes-Davis, Doug (High Plains Films, 2005)
Libby, Montana is a small logging and mining town. This documentary looks at Libby in the context of its being deemed by the E.P.A. as the worst case of community-wide exposure to a toxic substance in U.S. history. In the case of Libby, this substance is asbestos, and hundreds of the townsfolk are sick or have already died from exposure due to asbestos contamination of the W.C. Grace & Co.'s vermiculite mine. The film documents the stories of the people of Libby who have been affected by asbestos poisoning and emphasizes the plight of these people and their supporters to receive recognition of this local tragedy.